The Use of Wondershare Quiz Creator Evaluation Media to Improve Student Learning Outcomes in Citizenship Education Courses - Khoirunnisak, Anis; Kuncorowati, Puji Wulandari; Marzuki, Marzuki (Jurnal Pendidikan Indonesia, 2022)
This study aims to analyze the use of online-based Wondershare Quiz Creator evaluation media. This study used an experimental method consisting of two groups: the Pre-test and Post-test t groups. The population of this study amounted to 40 students. The sample was selected using a cluster random sampling technique. The data collection method in this research is the test. The technique used to analyze the data is inferential statistics. Data analysis showed a significant difference between the results of the Pre-test and Post-test t. the mean value of the Post-test was higher than the mean value of the Pre-test of the experimental group. The research results in the field prove that there is an effect of using online-based evaluations with online-based Wondershare Quiz Creator evaluation media. The use of online-based Wondershare Quiz Creator is more practical for creative fans that can increase student enthusiasm and learning outcomes. Therefore, the use of online-based Wondershare Quiz Creator evaluation media can be a solution to improving student learning outcomes. The use of online-based Wondershare Quiz Creator is more practical for creative fans that can increase student enthusiasm and learning outcomes. Therefore, the use of online-based Wondershare Quiz Creator evaluation media can be a solution to improving student learning outcomes. The use of online-based Wondershare Quiz Creator is more practical for creative fans that can increase student enthusiasm and learning outcomes. Therefore, the use of online-based Wondershare Quiz Creator evaluation media can be a solution to improving student learning outcomes.